Good Manufacturing Practice Validation and Radiation Dosimetry for the Clinical Application of a Novel α7-nAChR Radioligand: [11C]KIn83 - Zhisheng Jia; Martin Bolin; Anton Forsberg Morén; Prodip Datta; Heba Asem; Hans Ågren; Bengt Långström; Agneta Nordberg; Christer Halldin; Sangram Nag (Molecules)
Nicotinic acetylcholine receptor (α7-nAChR) plays a crucial role in cognitive functions like memory and attention. Positron emission tomography (PET) imaging of α7-nAChR is gaining attraction for understanding and monitoring central nervous system disorders, such as Alzheimer’s disease, Parkinson’s disease, and schizophrenia. We developed [11C]KIn83, a novel α7-nAChR radioligand, and evaluated its biological properties. This study focused on two objectives: (1) to validate its Good Manufacturing Practice (GMP)-compliant production, and (2) to assess the dosimetry of [11C]KIn83 using non-human primate (NHP) whole-body PET data. Radiolabeling and drug product delivery of [11C]KIn83 were conducted using an automated synthesis module within a controlled GMP environment. The quality control tests performed adhered to the European Pharmacopoeia guidelines. The production of [11C]KIn83 was validated according to GMP standards, encompassing automated synthesis and quality control measures. For the dosimetry assessment, two female cynomolgus monkeys underwent whole-body PET scans. The radioactivity values injected for [11C]KIn83 were 150 MBq and 155 MBq, respectively, with an estimated radiation dose of 0.0047 mSv/MBq. Our findings pave the way for future clinical studies that investigate the potential of [11C]KIn83 to measure α7-nAChR, aiding our understanding and possibly supporting diagnoses of different cognitive disorders.